Efficacy of Essential Nutrient Intake From Local Food Products Bada Fish (Rasbora Argyrotaenia) on The Nutritional Status of Stunting Toddlers - Eva Yuniritha; Sri Darningsih; Fathmawati; Ayu Rafyoni; Helmizar (Postgraduate, University of Mataram, 2025)
Stunting in toddlers poses a significant public health challenge worldwide, with Indonesia recording a prevalence of 27.70% in 2019. This research investigates the efficacy of essential nutrient intake from local food products, specifically Bada fish (Rasbora argyrotaenia), in improving the nutritional status of stunted toddlers. The study employs a three-phase experimental design: Phase I focuses on laboratory preparation of nutritional supplements; Phase II involves the development of standardized recipes for complementary foods; and Phase III implements a Single Blind Randomized Controlled Trial to assess intervention impacts. The target population consists of children under five living within the Ophir and Suka Menanti Health Center regions, with selection criteria rigorously defined. Ethical considerations were upheld throughout the study, adhering to relevant regulations. This investigation is poised to provide critical insights into leveraging local nutritional resources to address stunting in vulnerable populations. Data indicated significant post-intervention improvements in micronutrient adequacy (p<0.05), although overall energy and protein intake did not show significant changes (p>0.05). Nutritional assessments revealed enhanced weight-for-age and weight-for-height indices, while height-for-age scores showed no significant improvement, highlighting a potential limitation in the duration of the intervention. This study underscores the viability of incorporating fish-based supplements in dietary programs designed to address child malnutrition and suggests that sustained interventions, complemented by maternal education on nutritional practices, are crucial for promoting lasting health benefits.